Pinus wallichiana-synthesized silver nanoparticles as biomedical agents: in-vitro and in-vivo approach. Issue 2 (2nd April 2020) - Khan, Nazish; Khan, Ibrar; Nadhman, Akhtar; Azam, Sadiq; Ullah, Inam; Ahmad, Farhan; Khan, Hamid Ali
ABSTRACT: The current study aims to assess the aqueous extract of Pinus wallichiana stem for the synthesis of small spherical-shaped (10–30 nm) silver nanoparticles (AgNPs) and their in-vitro and in-vivo biomedical applications. The biosynthesized AgNPs were nonmutagenic and safe at all test doses as per Ames and acute toxicity assay (20, 40, 60, and 80 mg/kg). The percent writhing inhibitory effect generated by AgNPs was 42.51, 50.84, and 59.06 at test doses of 10, 20, and 30 mg/kg, respectively. The percent decreased in gastrointestinal tract motility observed was 41.34%, 32.69%, and 28.48% at 10, 20, and 30 mg/kg, respectively. They also showed a significant antipyretic effect after 1, 2, and 3 h in comparison to normal saline. The AgNPs of P. wallichiana showed good antibacterial activity against Acinetobacter baumannii (60% with MIC50  = 2.36 mg/ml and MBC = 5.0 mg/ml). These nanoparticles also possessed good antioxidant activity of 61.77 ± 0.828% and 70.25 ± 0.56% at 400 and 500 µg/ml, respectively and lack phytoagglutinin potential. Because of their high potency as biomedical agents, these nanoparticles can be a good alternative to the currently available drugs and approaches. GRAPHICAL ABSTRACT: UF0001